Strategi Pemasaran Babagrosir sebagai Fashion Islami di Media Online - Habibi, Abdul Kadir; Athok Murtadhlo (LPPM Stikosa-AWS, 2024)
This research raises the issue of Babagrosir's digital marketing strategy as Islamic fashion on social media. Utilizing Instagram social media as a tool to form and increase sales is the right thing. The purpose of this research is to understand and describe the digital marketing strategy carried out by Babagrosir to increase sales to the public. It is hoped that the results of this research will become a reference for future parties. This research uses descriptive qualitative research methods and is analyzed using Marketing Public Relations theory. Data was collected through interviews with informants, namely Babagrosir's manager and Babagrosir's Instagram admin. Apart from that, researchers also observed Instagram content. The results of the research also showed that Babagrosir carried out the three elements of Marketing Public Relations, namely: push strategy, pull strategy, pass strategy. Of these three things, Babagrosir did it well and also on target.